Social skills for kids : from making friends and problem - solving to self control and communication - Powers, Keri K. (Stoughton, Ma. : Adams Media, 2021)
n this book, you'll find games to encourage them in group settings, activities that you (or another caregiver) can do alone with your child, and ways to make the most of virtual interactions for social skill development. So whether you're looking for new activities to entertain a few friends during playtime, searching for fun (and educational) games you and your child can play together, or even interested in ways to include people you can't physically visit, Social Skills for Kids has all the tools you need to help your child develop the social skills they need to succeed"-- Provided by publisher